MiR-9-z/zp2, miR-3154-y/zp2, and miR-3533-y/zp3 participated in ovarian development and adaptation to salinity stress in spotted scat (Scatophagus argus) - Zhuoying Leng; Xinghua Lin; Yi Zhai; Hongjuan Shi; Dongneng Jiang; Mouyan Jiang; Huapu Chen; Tianli Wu; Siping Deng (Aquaculture Reports)
Zona Pellucida (Zp) proteins are intimately associated with the living environment and reproductive styles in fish. Environmental salinity has a pronounced effect on reproduction in the spotted scat (Scatophagus argus). However, the precise function of Zps in reproduction and their expression regulation during salinity stress remain unclear. Therefore, the ovarian miRNA sequence (miRNA-seq) and RNA sequence (RNA-seq) of spotted scat were analyzed after 20 days of treatment period at salinities of 5 ppt (low salinity group, LS), 25 ppt (control group, Ctrl), and 35 ppt (high salinity group, HS). The RNA-seq analysis revealed that 41 DEGs associated with reproduction, including zp2, zp3, wt1b, erα, pgr, and others, exhibited significant differences in the Ctrl vs. HS or Ctrl vs. LS comparisons. The Ctrl vs. LS and Ctrl vs. HS comparisons yielded 193 and 258 DEMs, respectively, according to miRNA-seq analysis. The visualized target relationships showed that zp2 and zp3, formed 12 target pairs with 11 different DEMs. Five miRNA-target gene pairs, miR-9-x/zp2, miR-9-z/zp2, miR-3154-y/zp2, miR-3533-y/zp3, and miR-365-y/zp3, were predicted at the sequence level after salinity stress. The result of qRT-PCR demonstrated that both zp2 and zp3 exhibited the highest expression levels in the ovary. The expression levels of zp2, zp3, miR-9-z, miR-3154-y, and miR-3533-y were higher in phase Ⅴ than in other phases of ovarian development. The expression levels of zp2, zp3, and miR-3154-y increased significantly, while the expression levels of miR-9-z and miR-3533-y remained unchanged after 17β-estradiol (E2) injection. The dual-luciferase reporter assay, together with the changes observed in zp2, zp3, miR-9-z, miR-3154-y, and miR-3533-y after low and high salt treatment, demonstrated that zp2 expression was regulated by miR-9-z and miR-3154-y, while zp3 was regulated by miR-3533-y. These results suggest that miR-9-z/zp2, miR-3154-y/zp2, and miR-3533-y/zp3 are involved in ovarian development and adaptation to salinity stress in spotted scat.